2018
DOI: 10.1108/cg-12-2017-0301
|View full text |Cite
|
Sign up to set email alerts
|

Foreign board members and firm innovativeness: an exploratory analysis for setting a research agenda

Abstract: Purpose This paper aims to assess the often repeated, but empirically unconfirmed, supposition that there is a positive connection between foreign board members (FBMs) and firm innovativeness and to set a research agenda for future studies on the topic. Design/methodology/approach The analyses are based on a large sample of firms within the European Union, utilizing patent and trademark data together with information on the national diversity of the boards. Findings The analyses confirm that there is a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 60 publications
(65 reference statements)
3
33
0
Order By: Relevance
“…This indicates the fact that there is an increase in the number of foreign members in the executive positions. The impact of ethnic diversity on innovation capability determined in this study is in parallel with the results of studies conducted by Miller and Triana (2009), Cook and Glass (2015) and Makkonen et al (2018).…”
Section: Discussionsupporting
confidence: 81%
“…This indicates the fact that there is an increase in the number of foreign members in the executive positions. The impact of ethnic diversity on innovation capability determined in this study is in parallel with the results of studies conducted by Miller and Triana (2009), Cook and Glass (2015) and Makkonen et al (2018).…”
Section: Discussionsupporting
confidence: 81%
“…This relationship stems from the different perspectives, skills and knowledge as well as varied values, norms and understanding that result from diversity on the board (Ruigrok et al 2007). Consequently, the presence of different culture on the board may enrich corporate decisions and foster a firm's disclosure (Ameer et al 2010;Makkonen et al 2018;Rao & Tilt, 2016).…”
Section: Board Diversitymentioning
confidence: 99%
“…Based on the resource-based view (RBV) theory, Kyaw et al (2017) demonstrated that a more diverse board is capable of attracting more resources. Diverse boards improve the firm's strategic decision quality (Rathnayaka Mudiyanselageb, 2018;Michelon and Parbonetti, 2012), identify and fulfill stakeholder's requirements (de Jong and van der Meer, 2017) and improve the firm's reputation and performance (Makkonen et al, 2018;Arora and Sharma, 2016) and global existence (Butler, 2012). Diversity in board composition ensures that novel ideas are brought forward by the board and that a variety of values and behaviors are represented (Murphy and McIntyre, 2007).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Prior literature supports the positive aspects of national diversity in a boardroom (Makkonen et al, 2018;Ameer et al, 2010). Based on the ideas of the RBV theory, Hsu et al (2013) argued that appointment of multinational directors on the board is one of the most valuable resources of any firm's improved CSR reporting.…”
Section: Corporate Board National Diversitymentioning
confidence: 99%